(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
Electromagnetically induced transparency (EIT) is experimentally studied in a rubidium vapour cell (without buffer gas, both \(^87\)Rb and \(^85\)Rb present according to their natural abundance) kept within two-layers of \(μ(μ)\)-metal shields to avoid the effect of Earth’s magnetic field on the energy levels of atomic rubidium. An external cavity diode laser (ECDL), used as a low power probe laser, is locked to the hyperfine cross-over peak of \(F = 2 → F’ = 2, 3\) transitions of \(^87\)Rb. The frequency of another ECDL, the pump laser, is set to scan the \(F=1 → F’ = 0, 1, 2\) transitions of \(^87\)Rb. These form the \(Λ\)-type six level system. In the V-type system, both the pump and the probe lasers share the same \(F = 2\) ground level. The probe beam coming out of the cell is detected by a low noise fast photodetector. The resulting spectra show signature of EIT in the "peak" for the \(Λ\)-type system and in the "dip" for the V-type system. Numerical calculation based simulated spectra are also compared with the experimental spectra. In both the cases very narrow EIT linewidth \((Γ_t < Γ)\) is observed even at high value of pump Rabi-frequency \((Ω_cΓ)\). Narrower value of EIT linewidth is due to Doppler averaging phenomena.